AN ANALYTICAL STUDY OF THE SEA WATER SLIME WITH REFERENCE TO BACTERIAL FLORA. - PILLAI, A. G GOPALAKRISHNA (Fishery Technology, 2017)
A detailed study of the primary film of slime with referenceto the bacterial flora, its quality and quantity, as observedon different material surfaces exposed to sea water is carriedout. A correlation has been established between bacteria andslime deposited on different surfaces.